(untitled) (CAHIERS MAGELLANES-NS, 2024)
Back ground: This study examined the associations between emerging lipid biomarkers, Carbamylated-LDL (C-LDL), and coronary artery disease (CAD). Globally, cardiovascular disease (CVD) continues to be the leading cause of death, with CAD playing a major role. Elevated carbamylated low-density lipoprotein (C-LDL) levels are one of the major risk factors for CAD. The development of atherosclerosis, a disorder marked by the buildup of lipid-laden plaques within artery walls, is linked to C-LDL and is known to cause decreased blood flow and possibly even heart attacks. High C-LDL levels have been strongly correlated with an increased incidence of CAD, as numerous investigations have shown. A number of therapeutic approaches have demonstrated effectiveness in lowering C-LDL levels and the risk of CAD, including lipid-lowering medications, statins, and lifestyle changes. This presentation highlights the continuous need for efficient therapeutic interventions by emphasizing the significance of C-LDL control in the prevention and treatment of CAD.